PERCEPTION OF STUDENTS ON THE EFFECTIVENESS OF USING GOOGLE CLASSROOM AS BASIC LEARNING IN AUTOMOTIVE BASIC ENGINEERING IN VOCATIONAL SCHOOL - Nur Arifin, Muhammad Zaki; Sukrawan, Yusep; Permana, Tatang; Sulaeman, Annisa Nur Fadillah (Universitas Pendidikan Indonesia, 2021)
This study aims to obtain data on the effectiveness of using google classroom in online learning for TDO subjects, perceptions and student learning outcomes. The research method used is descriptive quantitative method with ex post facto design. The research sample used purposive sampling, namely 40 students of class X TKRO A. The research instrument uses documentation and questionnaires. The results showed that students' perceptions of the learning process using google classroom on battery material were 66%. Student learning outcomes show as much as 77.5% have been completed. In general, learning by using google classroom on battery material achieves quite effective results.